KUALITAS BRIKET LIMBAH TEBANGAN KAYU GALAM SEBAGAI SUMBER ENERGI ALTERNATIF - Faiza Elisa Hasfianti; Endang Sriningsih; Diky Subhanuddin (Jurnal Penelitian Hasil Hutan, 2019)
Left over wood felling waste is an alternative sourcse for energy from forest biomass. This research is aiming tostudy the quality of briquettes made of left over galam wood felling as alternative energy raw material. Left overgalam wastes is in the form of stems, twigs, leaves, and bark of galam. The waste was burned into charcoal and grindthem into charcoal powder and formed into briquettes using a hydraulic press. The briquetting process wasconductedusing two variations in pressure and the percentage amount of adhesive mixed. The charcoal briquettes produced werethen analyzed for quality and it was compared to the Indonesian standards (SNI 01-6235-2000) and other qualitystandards for commercial briquettes. Results showed the calorific value at briquettes from stem, twigs, leaves and galambark between 5139.01–6948.50 cal/g, moisture content 3.91–24.45%, ash content 3.08–12.49%, and volatilematter 23.91–37.54%. In general the quality of galam wood briquettes shows a high heating value, so that it could beused as a new biomass-based alternative energy.